Plantar pressure is changed to increase post-impact ball speed during longline forehand and backhand groundstroke in elite female tennis players - Lambrich, J.; Muehlbauer, T. (Frontiers in Sports and Active Living, 2023)
Introduction: Achieving high ball speed during the execution of groundstrokes represents a performance-relevant factor in tennis. However, it is unclear how plantar pressure data undergo change during the execution of groundstrokes by tennis players to achieve high postimpact ball speed. Thus, the objective of the present study is to determine how tennis players change the plantar pressure in each foot when they execute longline forehand and backhand groundstrokes in order to increase postimpact ball speed.